Menopause hormone therapy: latest developments and clinical practice - Fait, Tomas (Drugs in context, 2019)
Menopause hormone therapy (MHT) is the most efficient treatment for symptoms of acute climacteric syndrome and for efficient prevention of long-term estrogen deficiency. Vaginal administration of low doses of estrogen is a therapy of choice for treatment and prevention of urogenital atrophy and its consequences. Systemic treatment may include estrogen, but an equally efficient alternative is tibolone. Nonhormonal therapy relies on phytoestrogens, black cohosh extract, and serotonin reuptake inhibitors.
Keywords: climacteric syndrome; tibolone; atrophic vaginitis; bazedoxifene; phytoestrogens; menopause hormone therapy